Are Commitment Profiles Stable and Predictable? A Latent Transition Analysis - Kam, C.; Morin, A.; Meyer, John; Topolnytsky, L. (2016)
Recent efforts have been made to identify and compare employees with profiles reflecting different combinations of affective (AC), normative (NC), and continuance (CC) organizational commitment. To date, the optimal profiles in terms of employee behavior and well-being have been found to be those in which AC, NC, and CC are all strong, or those where AC, or AC and NC, dominate. The poorest outcomes are found for profiles where AC, NC, and CC are all weak, or CC dominates. The primary goal of the current study was to use latent profile analysis and latent transition analysis to identify profile groups and examine changes in profile membership over an 8-month period in an organization undergoing a strategic change. We also tested hypotheses concerning the relation between perceived trustworthiness of management and employees’ commitment profile within and across time. We found that commitment profiles have substantial temporal stability and that trustworthiness positively predicts memberships in more desirable commitment profiles. There was also some, albeit weak, evidence that changes in perceived trustworthiness were accompanied by corresponding shifts in the commitment profile.